2018
DOI: 10.1039/c7gc02989f
|View full text |Cite
|
Sign up to set email alerts
|

Promising bulk production of a potentially benign bisphenol A replacement from a hardwood lignin platform

Abstract: A unique, bulk-scale lignin-to-chemicals valorisation chain converts economically feasible 4-n-propylsyringol into low-oestrogenic bisphenols suitable for aromatic polyesters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 82 publications
0
75
0
Order By: Relevance
“…Among others, ethyl-(EPs) and propylphenols (PPs) are common aromatics derived from lignin depolymerization and the gasification of coal [3,6,[21][22][23][24][25][26]. Alkylphenols have interesting application themselves like solvents, fuel and rubber additives, and thermosets [27][28][29][30][31]. Valorization of these alkylphenols into base chemicals like phenol and olefins is also relevant when they become abundantly available, but this synthetic pathway is underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, ethyl-(EPs) and propylphenols (PPs) are common aromatics derived from lignin depolymerization and the gasification of coal [3,6,[21][22][23][24][25][26]. Alkylphenols have interesting application themselves like solvents, fuel and rubber additives, and thermosets [27][28][29][30][31]. Valorization of these alkylphenols into base chemicals like phenol and olefins is also relevant when they become abundantly available, but this synthetic pathway is underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37] Yet, to the best of our knowledge, there is only one example where an actual lignin-derived monomer (4-npropylsyringnol, Figure 10C) was used. 38 Moreover, the authors conducted an early-stage economic assessment which showed that the scale-up of the bissyringol (Figure 10C) could be economically feasible. The comparison of BPA with the lignin-based BPA replacement shows two interesting features.…”
mentioning
confidence: 99%
“…This allowed more adequate benchmarking as thermal properties of PCs correlate with M w . 48 Strikingly, although previous reports revealed bimodal M w distributions for 4-alkylated poly(m,m′-BGF carbonate) that were hypothesised to be related to macrocycle formation, 34,35 here monomodal distributions were observed for all BGF-PCs, including homopolymeric m,p′-BGF-PC. Further research should unravel if this was indeed connected to m,m′-regioisomerism, or due to the type of phase-transfer catalyst used.…”
Section: Random Copolymerisation Into Aromatic Polycarbonate (Pc)mentioning
confidence: 74%
“…Firstly, as bio-based p,p′-BGF does only differ from petro-based p,p′-BPF in terms of its o-methoxy groups, these groups can be unambiguously identified as the root cause for the significant drop in in vitro oestrogenic activity, reducing both potency (by about two orders) and efficacy (by >50%). Noticeably, lower in vitro oestrogenic activities were already reported for 4-alkylated m,m′-BGFs and m,m′bissyringol Fs (BSFs), 34,35 although the hypothesised link with the methoxy groups could then not be unambiguously established due to the inaccessibility of non-methoxylated analogues. Taken together, these results clearly illustrate the positive effect of incorporating o-methoxy moieties into bisphenol scaffolds on lowering in vitro oestrogenic transactivation, both in terms of potency and efficacy.…”
Section: Papermentioning
confidence: 90%